2012
DOI: 10.1186/1748-717x-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Skin toxicity from external beam radiation therapy in breast cancer patients: protective effects of Resveratrol, Lycopene, Vitamin C and anthocianin (Ixor®)

Abstract: IntroductionThis is an observational study and the aim is to evaluate the effect of dietary supplements based on Resveratrol, Lycopene, Vitamin C and Anthocyanins (Ixor®) in reducing skin toxicity due to external beam radiotherapy in patients affected by breast cancer.Materials and methods71 patients were enrolled and they were divided in two different groups: a control group (CG) of 41 patients treated with prophylactic topical therapy based on hyaluronic acid and topical steroid therapy in case of occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In a study in human patients of breast cancer, the effect of dietary supplements based on RSV, lycopene, vitamin C and anthocyanins (Ixor ® ) in reducing skin toxicity, due to external beam XRT directed to the breast, was evaluated (Di Franco et al, 2012). In this study, all enrolled patients underwent conservative surgery (quadrantectomy), and the patients were subjected to adjuvant radiation treatment with 6 MV photons, with a dose of 50 Gy (2 Gy/fraction) directed to whole breast, and a subsequent additional dose of 10 Gy (2 Gy/fraction) directed to original tumour site.…”
Section: Breast Cancermentioning
confidence: 99%
“…In a study in human patients of breast cancer, the effect of dietary supplements based on RSV, lycopene, vitamin C and anthocyanins (Ixor ® ) in reducing skin toxicity, due to external beam XRT directed to the breast, was evaluated (Di Franco et al, 2012). In this study, all enrolled patients underwent conservative surgery (quadrantectomy), and the patients were subjected to adjuvant radiation treatment with 6 MV photons, with a dose of 50 Gy (2 Gy/fraction) directed to whole breast, and a subsequent additional dose of 10 Gy (2 Gy/fraction) directed to original tumour site.…”
Section: Breast Cancermentioning
confidence: 99%
“…These compounds were used at a dose of two tablets a day, starting from 10 days before the radiotherapy until 10 days after the end of treatment. 38 The studies of Zhang et al 39 demonstrated anticancer activities of tea epigallocatechin-3-gallate in breast cancer patients under radiotherapy. 43 At present, A. melanocarpa fruits are used for syrup, jam, juice, jellies, tea, wine, liqueur, and commercial extract (Aronox ® by Agropharm (Poland)) production.…”
Section: Dietary Antioxidants and Their Role In Cancermentioning
confidence: 98%
“…Moreover, it was used to reduce skin toxicity secondary to chemoradiation in patients with breast cancer [110,[116][117][118]. However, skin photoprotective effects determined by erythema, were only observed following at least 10 weeks of oral supplementation of several carotene including lycopene [60,112,114,[119][120][121][122][123].…”
Section: Can Skin Redox Balance Be Efficiently Affected By Exogenous mentioning
confidence: 99%